PENINGKATAN KETERAMPILAN LOKOMOTOR ANAK USIA 5- 6 TAHUN MELALUI GROSS MOTORSKILL PLAYMAT DI TK PARAS JAYA - Arta Shopia, Theresia; Septiani, Yin Yin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve locomotor skills of children aged 5–6 years through the use of a gross motor skill playmat at TK Paras Jaya, Palembang. Preliminary observations indicated that most children had not yet developed locomotor skills optimally due to limited outdoor facilities and the lack of varied, structured motor activities. The study involved 10 children in Group B1 and was conducted in January 2026 using the Kemmis and McTaggart action research model consisting of planning, action, observation, and reflection. Data were collected through observation checklists, documentation, and informal interviews. The locomotor indicators assessed were walking, running, jumping, tiptoeing, and hopping. Data analysis combined qualitative description and quantitative percentage calculations. The results showed a gradual improvement across cycles. In the pre-cycle stage, classical achievement was 45% (mostly in the category of Not Yet Developed). After Cycle I, children’s performance improved, although several indicators still required intensive guidance. In Cycle II, classical completeness reached 90%, with most children achieving the categories of Developing as Expected and Very Well Developed. The gross motor skill playmat effectively supported children’s balance, coordination, and motor control through structured and enjoyable play. Therefore, the playmat can be recommended as an alternative learning medium to enhance locomotor skills in early childhood.